COVID-19 vaccine booster dose acceptance among older adults - Sezerol, Mehmet Akif; Davun, Selin (MDPI, 2023)
This study aimed to determine the factors that cause individuals between the ages of 65 and 75 to not receive the third dose of a COVID-19 vaccination, to advise those who are hesitant, and to learn their thoughts about taking the third dose. (1) Material and Methods: This cross-sectional study was conducted between April and May 2022 among 2383 older adults aged between 65–75 who had never received a COVID-19 booster vaccination, according to the records of the District Health Directorate in the Sultanbeyli district of Istanbul. A three-part questionnaire prepared by researchers was given to the older adults via telephone. For statistical analysis of the data, the Chi-square test was used to compare variables; p < 0.05 was considered statistically significant. (2) Results: This research was completed with 1075 participants, reaching 45% of people aged 65–75 who did not receive the third dose of the COVID-19 vaccine in the region. In total, 64.2% of the participants were female and 35.8% were male, and the mean age was 69.33 ± 2.88. Those who had previously received an influenza vaccine were 1.9 times (95% CI 1.22–2.99) more likely to seek vaccination. Educational status also played a role, as older adults who were uneducated were 0.5 times (95% CI 0.42–0.76) less likely to seek vaccination. In addition, those who stated that lack of time was the reason for not vaccinating were 1.4 times (95% CI 1.01–1.98), and those who did not have it due to forgetting, 5.6 times (95% CI 2.58–12.24), more likely to seek vaccination. (3) Conclusion: This study shows, in detail, the importance of informing older adults, who have not received the third dose of vaccine for COVID-19 and who are in the risk group, as well as those who are not fully vaccinated, about the risks of not being vaccinated. We believe that it is important to vaccinate older patients; further, since immunity conferred by vaccination may decline over time, mortality rates decrease with the administration of additional doses.
Keywords: Acceptance; Booster Dose; COVID-19; Older Adults; Vaccine